Legal Analysis of the Imposition of Criminal Sentences for Fraud in Debt Agreement Cases: Case Study of Decision Number 331/PID.B/2021/PN JKT.BRT - Muharam, Irsan; Nardiman; Markoni; Kanthika, I Made (International Journal of Science and Society, 2024)
According to Article 1328 of the Civil Code, fraud is a defect of will, while Article 378 of the Criminal Code contains a series of words such as lies, deception, false circumstances, and false dignity. The consequences of fraud are a reason for cancelling the agreement. The problems raised in research on the imposition of criminal fraud in debt and receivable agreement cases. The method used in this research is normative juridical with descriptive-analytical specifications. The research results obtained first: The parameter that differentiates default from criminal acts of fraud is that default is seen from the good faith of the parties, whereas in criminal acts of fraud, it is motivated by evil intentions (mens rea) to possess objects (goods) belonging to other people as well as intentionally not fulfil his achievements. second: The debtor can only be criminally processed if an agreement meets the elements of fraud. If the debtor does not commit a series of lies to obtain a loan from the debtor, the debtor cannot be prosecuted under the threat of Article 378 of the Criminal Code regarding fraud. The debtor will be free from the threat of criminal penalties due to his inability to carry out the agreement's contents. In the case based on Decision Number 331/Pid.B/2021/Pn Jkt. Brt, the defendant committed an act through deception or a series of lies, encouraging other people to write off the receivables by giving 2 blank checks to pay the remaining loan which appeared to be -as if the Defendant's debt had been paid off. This is a legal event that can be tried through criminal justice.